Serological identification of MERS-CoV in camels of Wasit province, Iraq - Hala SR. AL-Taee; Azhar Ali Sekhi; Hasanain A.J. Gharban; Hussien M.A. Biati (Open Veterinary Journal, 2023)
Background: Since the first human case of Middle East Respiratory Syndrome (MERS) caused by Coronavirus (MERS-CoV) in 2012, several evidences base have shown one-humped camels as the main reservoir host, from which, infection transmit to humans. Aim: Serological investigation of MERS in dromedary camels in Wasit province (Iraq), detection severity of infection and association to some risk factors. Methods: A total of 455 dromedary camels were selected randomly from two main districts in Wasit province, Iraq during January and April (2023). Sera of all study camels were examined by ELISA, and titers of positive study animals were categorized according to its severity. Results: Serological testing yielded 37.58% positive animals for MERS infection. According to severity of positive ODs (titer), a total of 53.22%, 30.99%, 12.28%, and 3.51% were showed mild, moderate, strong and very strong infections, respectively. Regarding risk factors, significant elevation in seropositivity was seen in camels of  3-6 and  6 years old, and reduced in camels of  3 years old with elevated risk of MERS with increased age. Regionally, seropositivity and relative risk were increased in camels of Shaykh Sa'd when compared with Al-Numaniyah. Regarding sex, no significant variation was detected between seropositive females and males; however, male camels appeared at higher risk than females. Association between severity of MERS infection and risk factors revealed that there was a significant increase in mild and moderate infections in female camels of  6 years old; whereas, strong and very strong infections were seen in male camels of  3-6 years old. The mild and very strong infections were recorded in Shaykh Sa'd; while, moderate and strong infections in Al-Numaniyah. Conclusion: The study indicated a longstanding existence of MERS-CoV in camels of Wasit province, therefore, recent infections or active viral excretion are required for confirmation by molecular approaches. [Open Vet J 2023; 13(10.000): 1283-1289]